FAKTOR-FAKTOR YANG MEMPENGARUHI INISIASI MENYUSUI DINI DI PUSKESMAS PIJOR KOLING KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN TAHUN 2018 - Nurmala Nurmala; Elisabeth Dame Manalu; Selamat Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
The high rate of infant mortality and infant morbidity in Indonesia is still one of the health problems in Indonesia. One way to reduce the rate by early breastfeeding. In 2017 early breastfeeding initiation coverage in the area of public health center of early breastfeeding initiationThis research aims to impove the target perfromance of early breastfeeding in Pijor Koling Public Health Center. This research is survey analytic with cross sectional. The sampel of researah is 54 mothers who just giving birth baby. The analysis data use chi square test. The sampling technique is purposing sampling. The result of research indicate that there is meaningful between knowledge P=0,016 (P<0,05), occupation P=0,010 (P<0,05), the suppot of family p= 0,002 (p<0,05), attitude P=0,059 (P<0,05), Age P= 0,007 (P<0,05), and there is no relation between knowledge with culture. P=0,1000 (P>0,05), The result of regression logistict test show that the family support is having strongly relation with early breastfeeding initiation with the high of value 5,369 (95% CI: 1,178-22,056 Intiation as many as 5,098 times more bigger than mothers who have support family. The suggestion of Researcher to health workers of health of mother and child of Pijor Koling Public Health Center more increase information abaut early breastfeeding initiation to mothers who have no job.